A functionally adaptive MOF-derived zinc-based hybrid material and a method of making the same
Patent Information
- Application Number
- CN202611114240.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-23
AI Technical Summary
例如,Fe-MOF具有类过氧化物酶(POD)活性,可催化生成活性氧杀菌,但其缺乏类超氧化物歧化酶(SOD)活性,无法清除过量活性氧,易导致氧化应激损伤而阻碍骨修复
1、本发明提供的MOF衍生的锌基杂化材料,其包含锌元素、对苯二甲酸有机配体骨架以及磷酸根基团。该材料经水热反应将磷酸根基团引入MOF前驱体骨架中,红外光谱中于1565cm-1和1395cm-1处呈现羧酸根振动峰,于1030cm-1处呈现P-O键振动峰,于509~635cm-1处呈现Zn-O键和磷酸根基团振动峰,结构明确。
Smart Images

Figure CN122958710A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology related to orthopedic implant devices, specifically relating to a functionally adaptable MOF-derived zinc-based hybrid material and its preparation method. Background Technology
[0002] Fracture-related infection is a major complication leading to permanent functional loss or even amputation in patients after fracture surgery. Clinical statistics show that the infection rate after internal fixation of closed fractures is 1% to 2%, while the infection rate after complex open fractures is as high as 30%. Combined with the global base of 178 million new fracture cases each year, fracture-related infection has evolved into a global orthopedic clinical challenge.
[0003] Currently, the mainstream clinical interventions for fracture-related infections mainly involve systemic antibiotic infusion, local antibiotic administration, and antibiotic-impregnated bone cement implantation. While these methods can inhibit planktonic pathogens to some extent, they are insufficient to completely eliminate pathogens encapsulated in biofilms on the implant surface. Furthermore, antibiotic treatment is largely ineffective against infections caused by drug-resistant bacteria (such as methicillin-resistant Staphylococcus aureus), and high-dose antibiotics significantly inhibit bone remodeling and interfere with normal bone tissue repair, further prolonging the fracture healing period. Existing antibiotic therapies fail to fundamentally address the clinical challenges of treating and recurring fracture-related infections.
[0004] Metal-organic frameworks (MOFs), as enzyme-like catalytic functional materials, have attracted attention for constructing bioactive coatings with active antibacterial functions. For example, Fe-MOFs possess peroxidase (POD)-like activity, which can catalyze the generation of reactive oxygen species for sterilization; however, they lack superoxide dismutase (SOD)-like activity, failing to scavenge excess reactive oxygen species and easily leading to oxidative stress damage that hinders bone repair. Single-enzyme-like active materials cannot simultaneously meet the dual requirements of anti-infection and bone repair promotion, limiting their application in the surface modification of orthopedic implants. Summary of the Invention
[0005] The purpose of this invention is to provide a functionally adaptable MOF-derived zinc-based hybrid material and its preparation method.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A functionally adaptable MOF-derived zinc-based hybrid material, comprising zinc, a terephthalic acid organic ligand framework, and phosphate groups; the zinc-based hybrid material is prepared by the following method: a zinc source, terephthalic acid, and triethylamine are mixed and stirred in an organic solution to obtain a zinc-based MOF precursor; the zinc-based MOF precursor is mixed with sodium phosphate in an aqueous ethanol solution, and a hydrothermal reaction is carried out to introduce phosphate groups into the MOF precursor framework to obtain the zinc-based hybrid material.
[0007] Furthermore, when preparing the zinc-based MOF precursor, the mass ratio of zinc source to terephthalic acid is (1~3):1, and the mass ratio of triethylamine to terephthalic acid is (2~4):1; the organic solvent is N,N-dimethylformamide, and the stirring reaction time of the zinc-based MOF precursor is 2~4h.
[0008] Furthermore, the mass ratio of the zinc-based MOF precursor to sodium phosphate is (0.01~10):1, and the volume fraction of ethanol in the aqueous ethanol solution is 0~70%.
[0009] Furthermore, the hydrothermal reaction includes a heating stage and a heat preservation stage; the temperature of the heating stage is 160~180℃, the temperature of the heat preservation stage is 130~150℃, and the heat preservation time is 5~20h.
[0010] Furthermore, in the infrared spectrum of the zinc-based hybrid material, at 1565 cm⁻¹... -1 and 1395cm -1 It has a carboxylate vibration peak at 1030 cm⁻¹. -1 It has a PO bond vibration peak at 509~635 cm⁻¹. -1 It exhibits vibrational peaks of Zn-O bonds and phosphate groups.
[0011] A method for preparing a functionally adaptable MOF-derived zinc-based hybrid material includes the following steps: (1) Dissolve zinc source and terephthalic acid in an organic solvent, add triethylamine dropwise under stirring, and after continuous stirring, separate and dry to obtain zinc-based MOF precursor; (2) Disperse the precursor obtained in step (1) and sodium phosphate in an ethanol aqueous solution and stir to mix; (3) Place the mixture obtained in step (2) in a closed reaction vessel, heat it at 160~180℃ and then cool it down to 130~150℃ and keep it at the temperature for 5~20h. After the reaction is completed, separate, wash and dry to obtain the zinc-based hybrid material.
[0012] Furthermore, the zinc source in step (1) is zinc nitrate hexahydrate, and the organic solvent is N,N-dimethylformamide; the mass ratio of the zinc source to terephthalic acid is (1~3):1.
[0013] Furthermore, the mass ratio of triethylamine to terephthalic acid in step (1) is (2~4):1; the duration of the continuous stirring reaction is 2~4h.
[0014] Furthermore, in step (2), the mass ratio of the zinc-based MOF precursor to sodium phosphate is (0.01~10):1, and the volume fraction of ethanol in the aqueous ethanol solution is 0~70%.
[0015] Beneficial effects of this invention: 1. The MOF-derived zinc-based hybrid material provided by this invention comprises zinc, a terephthalic acid organic ligand framework, and phosphate groups. This material incorporates phosphate groups into the MOF precursor framework via a hydrothermal reaction, and its infrared spectrum is positive at 1565 cm⁻¹. -1 and 1395cm -1 The carboxylate vibration peak is observed at 1030 cm⁻¹. -1 The PO bond vibration peak is observed at 509–635 cm⁻¹. -1 The structure exhibits vibrational peaks of Zn-O bonds and phosphate groups, indicating a clear structure.
[0016] 2. In the preparation method of the material of the present invention, by controlling the mass ratio of zinc source to terephthalic acid to (1~3):1, the mass ratio of triethylamine to terephthalic acid to (2~4):1, and the stirring reaction time to 2~4h, the degree of introduction of zinc source into MOF can be controlled; by controlling the mass ratio of zinc-based MOF precursor to sodium phosphate to (0.01~10):1, the volume fraction of ethanol in the ethanol aqueous solution to 0~70%, and adopting a hydrothermal reaction including a heating stage and a heat preservation stage (heating stage 160~180℃, heat preservation stage 130~150℃, heat preservation 5~20h), the degree of introduction of phosphate groups into the precursor skeleton can be regulated, thereby obtaining a dual-enzyme functional material with both POD-like enzyme activity and SOD-like enzyme activity.
[0017] 3. This zinc-based hybrid material can catalyze the generation of reactive oxygen species from hydrogen peroxide for antibacterial purposes under POD-like enzyme activity, and simultaneously scavenge reactive oxygen species such as superoxide anions to avoid oxidative stress damage under SOD-like enzyme activity. This functional adaptation of dual enzyme activities enables it to promote bone repair while fighting infection, making it suitable as a functional coating for the surface of medical implants. Attached Figure Description
[0018] Figure 1 Morphology of MOF-derived zinc-based hybrid material (MOF-ZnP); Figure 2 Fourier transform infrared spectrum of MOF-ZnP; Figure 3 The kinetic curves of MOF-ZnP peroxidase (POD) activity at concentrations of 20, 50, and 100 μg / mL are shown. Figure 4 Bar chart showing the scavenging rate of superoxide anions by MOF-ZnP superoxide dismutase (SOD) at concentrations of 20, 50, and 100 μg / mL; Figure 5Images of bacterial colonies and antibacterial rates after co-culturing *Escherichia coli* and *Staphylococcus aureus* with ZnSO4 and MOF-ZnP at concentrations of 20, 50, and 100 μg / mL, respectively, for 24 h. Figure 5 (a) is an image of Escherichia coli colonies; Figure 5 (b) is a graph showing the antibacterial rate against Escherichia coli; Figure 5 (c) is an image of Staphylococcus aureus colonies; Figure 5 (d) is a graph showing the antibacterial rate against Staphylococcus aureus; Figure 6 The absorbance and relative cell proliferation rates of MC3T3-E1 osteoblasts after co-culturing with ZnSO4 and MOF-ZnP at concentrations of 20, 50, and 100 μg / mL for 1, 4, and 7 days are shown. Figure 6 (a) is the absorbance spectrum after co-culturing with ZnSO4. Figure 6 (b) A graph showing the relative proliferation rate of cells after co-culturing with ZnSO4; Figure 6 (c) is the absorbance spectrum after co-culturing with MOF-ZnP. Figure 6 (d) is a graph of the relative proliferation rate of cells after co-culturing with MOF-ZnP. Detailed Implementation
[0019] Example 1 100 mL of N,N-dimethylformamide (99.5% purity), 2.55 g of zinc nitrate hexahydrate (99% purity), and 1.275 g of terephthalic acid (99% purity) were added to a three-necked flask and stirred at room temperature until completely dissolved. 3.5 g of triethylamine was slowly added dropwise with stirring, and the reaction was continued for 2.5 h. The mixture was then vacuum filtered, and the filter cake was washed three times with N,N-dimethylformamide and dried at 120 °C to obtain the zinc-based MOF precursor.
[0020] The above precursor was mixed with sodium phosphate powder (98% purity) at a mass ratio of 1:1 and dispersed in a 30% (v / v) aqueous ethanol solution, and stirred for 1 h. The mixture was then transferred to a 50 mL hydrothermal reactor, heated to 160 °C in a drying oven, then cooled to 150 °C and maintained at that temperature for 15 h. After cooling to room temperature, the mixture was filtered, washed with distilled water, and dried at 100 °C to obtain the MOF-derived zinc-based hybrid material, designated MOF-ZnP-1.
[0021] Example 2 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-2. Its preparation method differs from Example 1 only in that the mass ratio of the zinc-based MOF precursor to sodium phosphate is 0.01:1. All other steps and parameters remain unchanged.
[0022] Example 3 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-3. Its preparation method differs from Example 1 only in that the mass ratio of the zinc-based MOF precursor to sodium phosphate is 0.1:1. All other steps and parameters remain unchanged.
[0023] Example 4 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-4. Its preparation method differs from Example 1 only in that the mass ratio of the zinc-based MOF precursor to sodium phosphate is 10:1. All other steps and parameters remain unchanged.
[0024] Example 5 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-5. Its preparation method differs from Example 1 only in that the hydrothermal reaction heating temperature is 180°C and the holding temperature is 150°C. All other steps and parameters remain unchanged.
[0025] Example 6 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-6. Its preparation method differs from Example 1 only in that the hydrothermal reaction heating temperature is 160°C and the holding temperature is 130°C. All other steps and parameters remain unchanged.
[0026] Example 7 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-7. Its preparation method differs from Example 1 only in that the reaction time is increased to 5 hours. All other steps and parameters remain unchanged.
[0027] Example 8 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-8. Its preparation method differs from Example 1 only in that the reaction time is increased to 20 hours. All other steps and parameters remain unchanged.
[0028] Example 9 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-9. Its preparation method differs from Example 1 only in that: in step (1), zinc nitrate hexahydrate is 1.275 g, triethylamine is 2.55 g, and the stirring reaction time is 2 h. All other steps and parameters remain unchanged.
[0029] Example 10 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-10. Its preparation method differs from Example 1 only in that: in step (1), zinc nitrate hexahydrate is 3.825 g, triethylamine is 5.1 g, and the stirring reaction time is 4 h. All other steps and parameters remain unchanged.
[0030] Example 11 This embodiment provides a MOF-derived zinc-based hybrid material, designated MOF-ZnP-11. Its preparation method differs from Example 1 only in that: the mass ratio of zinc-based MOF precursor to sodium phosphate is 10:1, and the volume fraction of ethanol is 70%; the hydrothermal reaction heating temperature is 180℃, the holding temperature is 150℃, and the holding time is 20h. All other steps and parameters remain unchanged.
[0031] Comparative Example 1 Zinc sulfate (99% purity), commercially available, product code ZnSO4.
[0032] Effect verification Using MOF-ZnP-1 prepared in Example 1 as the sample (hereinafter referred to as MOF-ZnP) and ZnSO4 of Comparative Example 1 as the control sample, the following tests were performed.
[0033] (1) Morphological structure Scanning electron microscopy was used for observation at an operating voltage of 20 kV and a working distance of 10 mm. The sample was observed directly while adhering to conductive adhesive. Figure 1 The results show that the MOF-ZnP particles are polyhedral in shape, with a size of 1~5μm, well dispersed, and without any adhering substances or secondary growth layers on the surface.
[0034] (2) Infrared spectrum Fourier transform infrared spectroscopy characteristics. Figure 2 Middle, 3444cm -1 The broad peak at 1565 cm⁻¹ is attributed to surface-adsorbed water or hydroxyl stretching vibrations. -1 and 1395cm -1 The absorption peaks at 1030 cm⁻¹ are attributed to the asymmetric and symmetric stretching vibrations of the carboxylate group, respectively; -1 The strong peak is attributed to the stretching vibration of the phosphate PO bond; 825 cm⁻¹ -1 and 745cm -1 The absorption peak at 509-635 cm⁻¹ is related to the out-of-plane bending vibration of the benzene ring CH; -1 The absorption peaks at that point are attributed to characteristic vibrations of the Zn-O coordination bond and phosphate group.
[0035] (3) Peroxidase-like activity Detection was performed using the TMB colorimetric method. 20 μg / mL, 50 μg / mL, and 100 μg / mL of MOF-ZnP were added to the system, and absorbance changes were monitored over 30 min. Figure 3 The results showed that MOF-ZnP exhibited POD-like enzyme activity at all three concentrations, with the activity increasing with increasing concentration.
[0036] (4) Superoxide dismutase-like activity WST-8 method detection. Figure 4The results showed that the scavenging rate of superoxide anions by MOF-ZnP increased with increasing concentration, reaching 56.38% at 100 μg / mL.
[0037] (5) Antibacterial properties The plate spread method was used, with *Escherichia coli* and *Staphylococcus aureus* as model strains. MOF-ZnP and ZnSO4 were prepared at concentrations of 20 μg / mL, 50 μg / mL, and 100 μg / mL, respectively, and were co-cultured with the strains for 24 h before counting. Figure 5 The results showed that MOF-ZnP had higher antibacterial rates against both bacteria than ZnSO4 at the same concentration, and these rates increased with increasing concentration. At 100 μg / mL, MOF-ZnP showed an antibacterial rate of 97.55% against Escherichia coli and 99.49% against Staphylococcus aureus; while ZnSO4 at the same concentration showed an antibacterial rate of 77.11% against Staphylococcus aureus.
[0038] (6) Cell compatibility CCK-8 assay, MC3T3-E1 osteoblasts. Cells were co-cultured with 20 μg / mL, 50 μg / mL and 100 μg / mL ZnSO4 and MOF-ZnP for 1 day, 4 days and 7 days respectively, and absorbance was measured to calculate relative proliferation rate. Figure 6 The results showed that when MOF-ZnP concentrations were 20 μg / mL and 50 μg / mL, the relative cell proliferation rate was above 80% throughout the culture period, with no cytotoxicity; however, at 100 μg / mL, the proliferation rate was below 80% after 4 and 7 days of culture. At all time points and concentrations, the relative cell proliferation rate of the MOF-ZnP group was higher than that of the ZnSO4 group at the same concentration, effectively promoting osteoblast proliferation.
[0039] The measured data in Example 1 show that after the phosphate group is introduced into the MOF backbone, the resulting material exhibits characteristic vibrational peaks of PO bond and phosphate group in the infrared spectrum, and simultaneously possesses POD-like and SOD-like enzyme activities. The antibacterial and cell compatibility results are consistent with the functional expectations of the above dual enzyme activities.
[0040] Examples 2 to 11 follow the same preparation route as Example 1—a zinc source, terephthalic acid, and triethylamine are reacted in N,N-dimethylformamide to obtain a MOF precursor, which is then reacted with sodium phosphate under hydrothermal conditions to introduce phosphate. The parameter adjustments involved in these examples, including variations in the mass ratio of zinc source to terephthalic acid (1–3:1), the mass ratio of triethylamine to terephthalic acid (2–4:1), the stirring reaction time (2–4 h), the mass ratio of precursor to sodium phosphate (0.01–10:1), the ethanol volume fraction (0–70%), the heating temperature (160–180 °C), the holding temperature (130–150 °C), and the holding time (5–20 h), do not alter the core reaction pathway of the two steps described above. Based on the general principles of MOF coordination assembly and hydrothermal ion exchange, variations within the above parameter range do not affect the coordination of terephthalic acid with zinc ions to form a backbone, nor do they prevent phosphate groups from substituting into the backbone. The infrared spectrum of the product will still exhibit carboxylate vibration peaks, PO bond vibration peaks, and Zn-O and phosphate group vibration peaks, thus retaining the structural basis required for dual enzyme activity. Therefore, the products of these examples can also possess both antibacterial and osteopromoting functions.
[0041] In summary, within the parameter range defined by this invention, the MOF-derived zinc-based hybrid materials prepared by the method all possess dual enzyme activities similar to POD and SOD, making them suitable as functional coatings for the surface of medical implantable devices.
[0042] The above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them; those skilled in the art can still modify the specific implementation of the present invention or make equivalent substitutions for some technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions claimed by the present invention.
Claims
1. A functionally adaptable MOF-derived zinc-based hybrid material, characterized in that, The zinc-based hybrid material comprises zinc, a terephthalic acid organic ligand framework, and phosphate groups. The zinc-based hybrid material is prepared by the following method: a zinc source, terephthalic acid, and triethylamine are mixed and stirred in an organic solution to obtain a zinc-based MOF precursor; the zinc-based MOF precursor is mixed with sodium phosphate in an ethanol aqueous solution; and the phosphate groups are introduced into the MOF precursor framework through a hydrothermal reaction to obtain the zinc-based hybrid material.
2. The functionally adaptable MOF-derived zinc-based hybrid material according to claim 1, characterized in that, When preparing the zinc-based MOF precursor, the mass ratio of zinc source to terephthalic acid is (1~3):1, the mass ratio of triethylamine to terephthalic acid is (2~4):1, the organic solvent is N,N-dimethylformamide, and the stirring reaction time of the zinc-based MOF precursor is 2~4h.
3. The functionally adaptable MOF-derived zinc-based hybrid material according to claim 1, characterized in that, The mass ratio of the zinc-based MOF precursor to sodium phosphate is (0.01~10):1, and the volume fraction of ethanol in the aqueous ethanol solution is 0~70%.
4. The functionally adaptable MOF-derived zinc-based hybrid material according to claim 1, characterized in that, The hydrothermal reaction includes a heating stage and a heat preservation stage; the temperature of the heating stage is 160~180℃, the temperature of the heat preservation stage is 130~150℃, and the heat preservation time is 5~20h.
5. The functionally adaptable MOF-derived zinc-based hybrid material according to claim 1, characterized in that, In the infrared spectrum of the zinc-based hybrid material, at 1565 cm⁻¹ -1 and 1395cm -1 It has a carboxylate vibration peak at 1030 cm⁻¹. -1 It has a PO bond vibration peak at 509~635 cm⁻¹. -1 It exhibits vibrational peaks of Zn-O bonds and phosphate groups.
6. A method for preparing a zinc-based hybrid material derived from a functionally adaptable MOF as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Dissolve zinc source and terephthalic acid in an organic solvent, add triethylamine dropwise under stirring, and after continuous stirring, separate and dry to obtain zinc-based MOF precursor; (2) Disperse the precursor obtained in step (1) and sodium phosphate in an ethanol aqueous solution and stir to mix; (3) Place the mixture obtained in step (2) in a closed reaction vessel, heat it at 160~180℃ and then cool it down to 130~150℃ and keep it at the temperature for 5~20h. After the reaction is completed, separate, wash and dry to obtain the zinc-based hybrid material.
7. The preparation method according to claim 6, characterized in that, The zinc source in step (1) is zinc nitrate hexahydrate, and the organic solvent is N,N-dimethylformamide; the mass ratio of the zinc source to terephthalic acid is (1~3):
1.
8. The preparation method according to claim 6, characterized in that, The mass ratio of triethylamine to terephthalic acid in step (1) is (2~4):1; the continuous stirring reaction time is 2~4h.
9. The preparation method according to claim 6, characterized in that, In step (2), the mass ratio of the zinc-based MOF precursor to sodium phosphate is (0.01~10):1, and the volume fraction of ethanol in the aqueous ethanol solution is 0~70%.